Unsung heroes in Sabah’s historiography: The indigenous community in the anti-Japanese movement in North Borneo, 1942–1945 - Md Saffie Abdul Rahim; Ramli Dollah; Eko Prayitno Joko (USM Press, 2024)
The Petagas War Memorial, erected in 1946, is the official symbol of Sabah’s anti-Japanese resistance between 1942 to 1945. The memorial focuses on the predominantly Chinese Kinabalu Guerrilla Defence Force (KGDF), which managed to secure vital assistance and cooperation from Sabah’s peribumi (indigenous) community. However, it does not adequately capture their contributions despite becoming the backbone of KGDF. Without them, the anti-Japanese movement would not have run smoothly nor achieved any form of success (albeit short-lived). On the 21st of January, the war memorial hosts an annual commemoration of KGDF against Japan. However, it tends to ignore the contributions of indigenous fighters. Therefore, this study seeks to examine the recognition that should have been given to Sabah’s indigenous fighters against the Japanese occupation in Sabah, exploring the cooperation between Sabah’s indigenous community and the KGDF in the anti-Japanese movement between 1942 and 1945. The aim is to place the role of former fighters in its proper context. This study is based on library research as well as interviews. The primary resources from the library research are derived from reports, files and newspapers found in the Sabah State Archives. Interviews are utilised to complement archival sources, especially in the absence of written records.